Investigation of Consumer Attitudes from the Perspective of Consumer Based Brand Equity on Tracksuit Brands - Yavuz Yıldız; Alper Kinden (Lithuanian Sports University, 2018)
Background.  Brand  equity  has  a  positive  impact  on  consumers'  selection  of  products  and  services,  their perception, purchasing intentions, their willingness to pay more for brands. Brand equity is designed to reflect the real value from the perspective of consumer that a brand name holds for the products and services. Measuring brand equity is important because brands are believed to be strong influencers of business outcomes, such as sales and market share. The aim of this study was to describe the brand equity of tracksuits and investigate the purchasing behaviours of the tracksuit consumers. Methods. The  research  sample  consisted  of  250  athletes  who  were  selected  via  random  sampling  method. "Consumer-Based Brand Equity Scale", developed by Vazquez, del Rio, and Iglesias (2002), was implemented in order to measure consumer-based brand equity with regard to tracksuit brands. Results.  Results  of  the  study  showed  that  the  consumer  based  brand  equity  did  not  differ  by  gender,  age, tracksuit usage purpose, tracksuit buying timing. However, it was found that the consumer based brand equity was significantly different in the number of tracksuits owned and the amount of payment. Conclusion.  High brand equity brings the willingness to pay more for that brand. Consequently, it can be suggested that high level of consumer based brand equity enhances the amount of purchases and willingness to pay more. Although there are many studies on the brand equity in sports, such as shoes and teams, we have found no research on tracksuits. This research focuses on tracksuits' brand equity. The results of this research contribute to sports marketing literature. Keywords:  sport, sports marketing, brand equity, tracksuit.